Dampak Transformasi Digitalisasi terhadap Perubahan Perilaku Masyarakat Pedesaan - Sari, Jayanti Armida; Diana, Bambang Agus (Jurnal Pemerintahan dan Politik, 2024)
The advancement of digitalization has significantly influenced the behaviors and culture of rural communities. This research aims to provide an in-depth insight into the complexity of the impact of digital transformation on the behaviors and culture of rural communities while highlighting the importance of addressing these challenges wisely and proactively. The research methodology employed in this study is descriptive qualitative with a literature review approach. Through literature analysis, this study explores various impacts of digitalization transformation on rural communities in Indonesia, including access to new information, economic opportunities, changes in behaviour regarding information access, communication, education, agriculture, healthcare, and economic empowerment. Findings indicate that digitalization has opened access to information and new economic opportunities for rural communities, mainly through the widespread penetration of the Internet and the adoption of digital technologies. Furthermore, changes in the behavior of rural communities occur across various aspects of life, including communication, education, healthcare, and agriculture. Despite the benefits of digitalization, efforts must mitigate adverse impacts such as online fraud and the spread of false information. Therefore, inclusive, and sustainable strategies for digital village development and increasing digital literacy are crucial in maximizing the benefits of rural digitalization in the future.